(untitled) - Poliak, Milos (Doprava a spoje, 2010)
The main purpose of paper was to consider influence of traffic politics on traffic economy. The paper is specialized on comparison road transport and rail transport. At first apprises of legislation within the validity European unit and on the territory of Slovak republic. By reason of advisement of tax burden in varied traffics, there is concrete model transit. It mentions on items of tax burden in varied types of traffic as an amount of items. On the ground of results, which are acquired from comparison road traffic and railage, there are created applications, which are advisable for solution of arose situation and confronts results with considered purposes from preclusion